2021
DOI: 10.3390/metabo11060362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Salivary Microorganisms and Metabolites Associated with Halitosis

Abstract: Halitosis is mainly caused by the action of oral microbes. The purpose of this study was to investigate the differences in salivary microbes and metabolites between subjects with and without halitosis. Of the 52 participants, 22 were classified into the halitosis group by the volatile sulfur compound analysis on breath samples. The 16S rRNA gene amplicon sequencing and metabolomics approaches were used to investigate the difference in microbes and metabolites in saliva of the control and halitosis groups. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
1
6
0
5
Order By: Relevance
“…Moreover, both genera correlated with increased VSC (here: H 2 S and CH 3 SH) values. This observation was in line with a Korean study where higher abundances of Prevotella and Alloprevotella in saliva correlated with amine metabolites, suggesting a causative mechanism via cadaverine and putrescine pathways [ 173 ].…”
Section: Prevotella Involvement In Oral Conditions Of Clinic...supporting
confidence: 91%
“…Moreover, both genera correlated with increased VSC (here: H 2 S and CH 3 SH) values. This observation was in line with a Korean study where higher abundances of Prevotella and Alloprevotella in saliva correlated with amine metabolites, suggesting a causative mechanism via cadaverine and putrescine pathways [ 173 ].…”
Section: Prevotella Involvement In Oral Conditions Of Clinic...supporting
confidence: 91%
“…Other studies have used isopropanol [ 208 ] or acetone [ 209 ], which requires evaporation and resuspension in an appropriate solvent before chromatographic analysis. When GC–MS is used, the dried extracts are derivatized using oximation followed by a silylation step [ 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. Methods involving headspace [ 217 ] and solid-phase microextraction (SPME) for VOC analysis [ 218 ] are also found.…”
Section: Underexplored Specimens In Clinical Metabolomicsmentioning
confidence: 99%
“…It is mostly GC–MS detection that is used for studying the VOCs present in saliva. This technique has already been applied in halitosis research, where a study recently identified two potential biomarkers of halitosis: 5-aminovaleric acid and N -acetylornithine [ 131 ]. Monedeiro et al have reported 164 VOCs in saliva, which they monitored by headspace solid-phase microextraction coupled to GC–MS (HS-SPME-GC–MS).…”
Section: Assessment Of Halitosismentioning
confidence: 99%